Gene regulatory networks: co-expression modules of protein coding genes and small RNAS governing essential biological processes in Coffea arabica L. - Ribeiro, Thales Henrique Cherubino (2023)
Coffee plants are the source of one of the most world-wide traded commodities. From harvesting, though processing to commercializing the coffee bean moves an international market that supports the livelihood of millions. The progressing understanding of how plants function at a cellular, molecular, and physiological level has enabled successive technological breakthroughs, this, in turn, has allowed a positive balance between the supply and demand for food. These successive breakthroughs of frontiers in agricultural knowledge are taking place along centuries of civilization. At this point, one of the most relevant frontiers of biology is at the molecular level. The understanding of how plants organize their physiological processes at the molecular level may be the way to finally balance agriculture with sustainable development. Advances in molecular biology are making this understanding possible by investigating how complex networks of regulatory elements coordinate the functioning of plants and other organisms. This thesis has the objective of contributing to the effort of revealing the functional dynamics of Coffea arabica metabolism using integrated biological data. From genome and transcriptome sequencing data of coffee samples, I was able to identify evolutionary phenomena such as gene balance, to predict and ascertain for the presence of metabolites, and to reveal multiple types of RNAs involved in control and/or developmental processes of flowering in Coffea arabica. Our discoveries regarding the organization and possible evolutionary trends of this genome can guide future works with the objective of maintaining the continuity of coffee.